Dictionary of the New Testament use of the Old Testament - Beale, G. K. (Gregory K.), 1949-; Carson, D. A. (Donald Arthur), 1946-; Gladd, Benjamin L.; Naselli, Andrew David, 1980- (2023)
"This companion volume to the Commentary on the New Testament Use of the Old Testament covers a range of interpretive topics and includes summary articles on each biblical book and numerous themes"--
Includes bibliographical references and index.
Keywords: Bible. -- Dictionaries; Bible. -- Relation to the Old Testament